Co-regulatory effects of hormone and mRNA–miRNA module on flower bud formation of Camellia oleifera - Du, Wei; Ding, Jian; Li, Jingbin; Li, He; Ruan, Chengjiang (Frontiers in Plant Science, 2023)
Few flower buds in a high-yield year are the main factors restricting the yield of Camellia oleifera in the next year. However, there are no relevant reports on the regulation mechanism of flower bud formation. In this study, hormones, mRNAs, and miRNAs were tested during flower bud formation in MY3 (“Min Yu 3,” with stable yield in different years) and QY2 (“Qian Yu 2,” with less flower bud formation in a high-yield year) cultivars. The results showed that except for IAA, the hormone contents of GA3, ABA, tZ, JA, and SA in the buds were higher than those in the fruit, and the contents of all hormones in the buds were higher than those in the adjacent tissues. This excluded the effect of hormones produced from the fruit on flower bud formation. The difference in hormones showed that 21–30 April was the critical period for flower bud formation in C. oleifera; the JA content in MY3 was higher than that in QY2, but a lower concentration of GA3 contributed to the formation of the C. oleifera flower bud. JA and GA3 might have different effects on flower bud formation. Comprehensive analysis of the RNA-seq data showed that differentially expressed genes were notably enriched in hormone signal transduction and the circadian system. Flower bud formation in MY3 was induced through the plant hormone receptor TIR1 (transport inhibitor response 1) of the IAA signaling pathway, the miR535-GID1c module of the GA signaling pathway, and the miR395-JAZ module of the JA signaling pathway. In addition, the expression of core clock components GI (GIGANTEA) and CO (CONSTANS) in MY3 increased 2.3-fold and 1.8-fold over that in QY2, respectively, indicating that the circadian system also played a role in promoting flower bud formation in MY3. Finally, the hormone signaling pathway and circadian system transmitted flowering signals to the floral meristem characteristic genes LFY (LEAFY) and AP1 (APETALA 1) via FT (FLOWERING LOCUS T) and SOC1 (SUPPRESSOR OF OVEREXPRESSION OF CO 1) to regulate flower bud formation. These data will provide the basis for understanding the mechanism of flower bud alternate formation and formulating high yield regulation measures for C. oleifera.